Textile production and consumption in the ancient Near East: archaeology, epigraphy, iconography - Nosch, Marie-Louise (Ancient textiles series, 2013)
In the past, textile production was a key part of all ancient societies. The Ancient Near East stands out in this respect with the overwhelming amount of documentation both in terms of raw materials, line of production, and the distribution of finished products. The thirteen intriguing chapters in Textile Production and Consumption in the Ancient Near East describe the developments and changes from household to standardised, industrialised and centralised productions which take place in the region. They discuss the economic, social and cultural impact of textiles on ancient society through the application of textile tool studies, experimental testing, context studies and epigraphical as well0as iconographical sources. Together they demonstrate that the textile industries, production, technology, consumption and innovations are crucial to, and therefore provide an indepth view of ancient societies during this period.0